Healthcare Students' Knowledge and Distrust of COVID-19 Conspiracy Theories - Fauzi, Ahmad; Sondakh, Jenny J. S.; Saleem, Maryam (Journal of Public Health for Tropical and Coastal Region, 2022)
Introduction: The spread of various conspiracy theories (CT) is one of the causes of the difficulty in handling the COVID-19 pandemic. The purpose of this study was to analyze the level of knowledge and distrust of healthcare students towards CT about COVID-19 and analyze what factors influence it.Methods : This survey research involved 230 health students from higher education institution in Malang. The respondents were selected through purposive sampling techniques. Data collection used a questionnaire which was distributed online. The data collected were analyzed using descriptive statistical techniques, one-way ANOVA test, LSD test, Pearson correlation test, and calculation of the coefficient of determination.Results: A total of 47.83% of students had knowledge scores that were in the good category, while only 7.39% of students had their CT scores in the good category. Length of study, degree program, and institution type have a significant effect on student knowledge, but CT scores were only influenced by institution type. Student knowledge was not significantly correlated to their distrust of CT about COVID-19.Conclusion: The majority of health students still believe CT about COVID-19. Considering the findings, it is necessary to reformulate the curriculum for healthcare education to prepare the next pandemic.